2016
DOI: 10.1007/s00702-016-1553-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of ASTN2 variants in childhood and adult ADHD, comorbid disorders and associated personality traits

Abstract: Previous linkage and genome wide association (GWA) studies in ADHD indicated astrotactin 2 (ASTN2) as a candidate gene for attention-deficit/hyperactivity disorder (ADHD). ASTN2 plays a key role in glial-guided neuronal migration. To investigate whether common variants in ASTN2 contribute to ADHD disorder risk, we tested 63 SNPs spanning ASTN2 for association with ADHD and specific comorbid disorders in two samples: 171 families of children with ADHD and their parents (N = 592), and an adult sample comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Defects in neuronal migration can cause a number of human developmental malformations (41,42). Given the evidence from animal models that Astn1 and possibly Astn2 are required for glial-guided neuronal migration, the involvement of astrotactins in human CNS disorders has been an object of intense interest for the past decade (8)(9)(10)(11)(43)(44)(45). Several linkage studies have suggested a possible role of astrotactins in neurodevelopmental and neurodegenerative disease.…”
Section: Astrotactins and Human Diseasementioning
confidence: 99%
“…Defects in neuronal migration can cause a number of human developmental malformations (41,42). Given the evidence from animal models that Astn1 and possibly Astn2 are required for glial-guided neuronal migration, the involvement of astrotactins in human CNS disorders has been an object of intense interest for the past decade (8)(9)(10)(11)(43)(44)(45). Several linkage studies have suggested a possible role of astrotactins in neurodevelopmental and neurodegenerative disease.…”
Section: Astrotactins and Human Diseasementioning
confidence: 99%
“…It has been reported that Astn2 attended neuronal migration [67] and surface protein trafficking [68]. ASTN2 is also widely proven to be associated with a number of mental illnesses in humans [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and has exhibited a relationship with hippocampus volume [69,70]. A previous study showed that the double knockout of the exon 5 of Astn2 and Fz6 (Frizzled6) led to a 180° hair orientation reversal on the back of mice [71]; however, no behavioral phenotype of Astn2 has yet been found in mutant or knockout mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…S9), indicating the core role of behavioral modification in mice domestication. Worthy of mention is that some PSGs without known behavioral phenotypes are associated with human mental illnesses, e.g., CBLN4 (Alzheimer's disease [33]), WBSCR17 (Parkinson's disease [34,35], autism [36]), and ASTN2 (autism [37][38][39][40][41][42], Alzheimer's disease [43,44], intellectual disability [45,46], schizophrenia [47,48], and attention deficit/hyperactivity disorder [40,[49][50][51]).…”
Section: Psgs Closely Related To the Function Of The Nervous Systemmentioning
confidence: 99%
“…Together with astrotactin 1, astrotactin 2 plays a key role in glial‐guided neuronal migration during development of the laminar architecture of cortical regions of the mammalian brain 23,24 . Some researchers reported that certain variants of the ASTN2 gene might be associated with the development of neuropsychiatric disorders, such as autism spectrum disorder, attention‐deficit/hyperactivity disorder, anxiety, obsessive‐compulsive disorder, schizophrenia, and Alzheimer's disease, 25–27 although others did not find such associations between ASTN2 gene variants and neuropsychiatric disorders 28 . A substantial number of studies have shown or suggested interactions between these neuropsychiatric disorders and alterations of opioid system function 29–32 .…”
Section: Discussionmentioning
confidence: 99%